Kontrol Suhu Otomatis Oven Vulkanisasi Konvensional di Laboratorium Unit Produksi Serabut Kelapa Berkaret - Nurjan Didik Purwanto; Puji Wiyono; Andika Wahyu Pratama (Jurusan Teknologi Pertanian, 2020)
The vulcanization process is a chemical reaction between rubber and sulfur to form cross-links and produce a three-dimensional structure. Temperature control in the vulcanization process is important to support the quality of the goods produced. In the coconut coir rubber production unit laboratory, the vulcanization oven is still conventional and manual for temperature control, therefore an operator is required to be on standby when the vulcanization oven is operated. The negligence of the operator will be fatal both in terms of the quality of the rubberised coir produced and the risk of fire. One of the causes of frequent fires in vulcanization ovens is the difficulty in setting the temperature in the oven process. To anticipate the occurrence of fires in the vulcanization oven, it is necessary to modify and add a temperature control to the oven. Based on the above problems, modifications need to be made which include the addition of a temperature control system and fire protection that combines temperature control, electric motor, fan, and indicator sirens in rubberized coconut fiber ovens so that the quality of the products produced remains good and avoids fire hazards. With this system, it is hoped that it can provide a sense of security and comfort for operators and contribute to the world of education, especially for students of the Agricultural Mechanization Study Program and other study programs at Lampung State Polytechnic. Automatic Temperature Control of Conventional Vulcanization Ovens in the Rubber Coir Production Unit Laboratory